High carbohydrate diet induced hypokalemic periodic paralysis: A case report - Shah, Shikha K.; Prasad, Ankit (Journal of Nepalese Society of Critical Care Medicine, 2024)
Hypokalemic periodic paralysis (HypoKPP) is a rare disorder characterised by the sudden onset of muscle weakness associated with low serum potassium levels. A 54-year-old man was admitted to the hospital with an abrupt onset of weakness in his right upper and lower extremities which slowly progressed to involve his left upper and lower extremities. He reported having consumed a carbohydrate-rich meal the day before the episode. Laboratory tests indicated severe hypokalemia with a serum potassium level of 2.3 mEq/L. He was treated with intravenous potassium chloride and his paralysis resolved after correction of hypokalemia. The patient was discharged on potassium supplementation and dietary guidelines were advised.